Sexual harassment in nightlife entertainment spots in Pomurje - Bulovec, Tinkara; Eman, Katja (Anali PAZU HD, 2022)
Existing data on the number of sexual harassment incidents represent only the tip of the iceberg, as victims most often do not report incidents of sexual harassment to the competent authorities. Mentioned leads to the emergence of a dark field of unreported crime. The latter is also affected by the outbreak of the COVID-19 pandemic and the accompanying security measures, which have caused young people’s parties movement from public events and bars to private spaces. (Young) Pomurje residents participate in various events during the nightlife, both in their home region and elsewhere in Slovenia. Consequently, they can (possibly) become victims of different forms of (sexual) harassment, which the authors discuss in the article.